Frontline Science: Elevated nuclear lamin A is permissive for granulocyte transendothelial migration but not for motility through collagen I barriers. Issue 2 (30th March 2018) - Yadav, Sandeep Kumar; Feigelson, Sara W.; Roncato, Francesco; Antman‐Passig, Merav; Shefi, Orit; Lammerding, Jan; Alon, Ronen
Abstract: Transendothelial migration (TEM) of lymphocytes and neutrophils is associated with the ability of their deformable nuclei to displace endothelial cytoskeletal barriers. Lamin A is a key intermediate filament component of the nuclear lamina that is downregulated during granulopoiesis. When elevated, lamin A restricts nuclear squeezing through rigid confinements. To determine if the low lamin A expression by leukocyte nuclei is critical for their exceptional squeezing ability through endothelial barriers, we overexpressed this protein in granulocyte‐like differentiated HL‐60 cells. A 10‐fold higher lamin A expression did not interfere with chemokinetic motility of these granulocytes on immobilized CXCL1. Furthermore, these lamin A high leukocytes exhibited normal chemotaxis toward CXCL1 determined in large pore transwell barriers, but poorly squeezed through 3 μm pores toward identical CXCL1 gradients. Strikingly, however, these leukocytes successfully completed paracellular TEM across inflamed endothelial monolayers under shear flow, albeit with a small delay in nuclear squeezing into their sub‐endothelial pseudopodia. In contrast, CXCR2 mediated granulocyte motility through collagen I barriers was dramatically delayed by lamin A overexpression due to a failure of lamin A high nuclei to translocate into the pseudopodia of the granulocytes. Collectively, our data predict that leukocytes maintain a low lamin A content in their nuclear lamina in order to optimize squeezing through extracellular collagen barriers but can tolerate high lamin A content when crossing the highly adaptable barriers presented by the endothelial cytoskeleton. Abstract : Differential effects of nuclear stiffness on chemokine‐driven leukocyte squeezing through endothelial and extracellular collagenous barriers.